Frazzled : Minor Incidents and Absolute Uncertainties - Vivat, Booki (New York, NY Harper, 2019)
When Abbie Wu goes to "Outdoor School," with her older brother as a counselor, she is torn between excitement and anxiety but decides to make it a life-changing adventure
Accelerated Reader AR
Reading Counts
Lexile
111113
Keywords: School field trips -- Juvenile fiction; Camps -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Siblings -- Juvenile fiction; Anxiety -- Juvenile fiction; School field trips -- Fiction; Camps -- Fiction; Middle schools -- Fiction; Brothers and sisters -- Fiction; Juvenile Fiction -- Social Issues -- Self-Esteem & Self-Reliance.; Juvenile Fiction -- School & Education; Children's stories; Humorous fiction; Bildungsromans; Fiction; Juvenile works